Research of Steady State Temperature Field of Spiral Bevel Gear with Different Tooth Surface Structures - Hui Cheng; Zhouyang Li; Sanmin Wang (Jixie chuandong)
A thermal network model of the helicopter main reducer under high-speed and heavy-load conditions is established，and the law of the temperature field of the spiral bevel gear with different tooth surface structures is obtained. Load contact analysis （LTCA） on the tooth surface of the spiral bevel gear based on the active design is performed to obtain the load between the teeth. Also，the friction coefficient and thermal load of the bevel gear are obtained by tribology and heat transfer. And the influence law of the direction of the bevel gear tooth surface contact trace，the length of the semi-major axis of the contact ellipse and the first derivative of the transmission ratio on the temperature field of the bevel gear is studied and analyzed.